(untitled) (Swiss Medical Weekly, 2024)
Cardiac amyloidosis is a disease characterised by the accumulation of amyloid protein in the heart tissue. There are several types of amyloidosis, but the most common types affecting the heart are ATTR amyloidosis (caused by transthyretin protein) and AL amyloidosis (caused by abnormal immunoglobulin light chains). Cardiac amyloidosis causes typical signs and symptoms of heart failure. Diagnosis involves a combination of imaging tests such as echocardiography and cardiac magnetic resonance imaging, as well as nuclear imaging scans and tissue biopsies to confirm the presence of amyloid deposits in the heart. Treatment of cardiac amyloidosis depends on the type and severity of the disease and includes medications to manage symptoms as well as treatments targeting the underlying cause of amyloidosis. Importantly, cardiac amyloidosis is a serious condition requiring specialised care from a multidisciplinary team including cardiologists and haematologists as well as other specialists familiar with the management of this rare disease. This is crucial, as early diagnosis and treatment are important for improving outcomes.